Ertapenem for the treatment of urinary tract infections caused by extended-spectrum beta-lactamase-producing bacteria in children - SANCAR, MESUT (INFORMA HEALTHCARE, 2011)
Background: Urinary tract infections (UTIs) are a problem frequently encountered by paediatric healthcare providers. Recent data suggest that extended-spectrum beta-lactamase (ESBL)-producing bacteria are an emerging cause of UTIs in non-hospitalized patients. We report our experience of ertapenem use in 50 patients with complicated UTIs, mainly pyelonephritis, caused by ESBL-producing organisms. Methods: Fifty patients aged < 16 y who had a complicated UTI caused by ESBL-producing organisms and who were treated with ertapenem at our hospital from 1 January 2009 to 31 December 2009, were included in the study. Results: There were 20 (40%) males and 30 (60%) females with a mean +/- standard deviation age of 38.6 +/- 36.9 months (range 6-156 months). Twenty-eight patients had no urological abnormality. In 40 patients ertapenem was initiated after results of microbiological cultures became available. Ertapenem was initiated empirically for 10 patients known to be colonized with ESBL-producing bacteria. Urine cultures were negative at 3.3 +/- 0.7 days (range 2-5 days) after starting ertapenem treatment. The mean duration of ertapenem treatment was 7.8 +/- 1.2 days (range 7-14 days). No laboratory or clinical side effects were observed. Conclusions: Ertapenem is promising for the culture-guided treatment of ESBL-producing Gram-negative complicated UTIs. Well-designed prospective studies are needed to define the role of ertapenem in treating complicated paediatric UTIs, especially upper UTIs.
Keywords: Ertapenem; paediatric; ESBL; urinary tract infection; COMMUNITY-ACQUIRED PNEUMONIA; ESCHERICHIA-COLI; NONHOSPITALIZED PATIENTS; DOUBLE-BLIND; INTRAABDOMINAL INFECTIONS; CLINICAL-FEATURES; IN-VITRO; ENTEROBACTERIACEAE; CEFTRIAXONE; RESISTANCE